Phase transformations and physico-mechanical properties of ceramic tiles from Lower Amu Darya raw materials for sustainable construction in earth and environmental engineering - Boyjanov Islom; Djabberganov Djakhangir; Matyaqubova Karomat; Khudayberganov Erkaboy; Sitmuratov Tulkinbek (E3S Web of Conferences)
This work investigates the physico-mechanical characteristics and phase transformations of ceramic tiles fabricated from local raw materials in the Lower Amu Darya region of Uzbekistan—specifically, clay from the Kulatau deposit and dune sand from the Tuprak-Kala massif. Laboratory- and industrial-scale experiments showed that an optimized composition, M-7, can be employed to produce unglazed facade and floor tiles fired at 1000°C and 1050°C. Under the same conditions, composition M-9 yields glazed facing and facade tiles with an opaque finish. The phase composition of the tiles includes mullite, anorthite, quartz, hematite, and a glassy phase, indicating that the mineral components significantly influence crystal growth and enhance physico-mechanical properties. These findings support the advancement of sustainable construction materials and resource-efficient practices within Earth and environmental engineering.